'Thinking Technology' in mature industry firms: understanding technology entrepreneurship. (4th August 2014) - Jelinek, Mariann
Technological entrepreneurship is important yet difficult in mature industry firms because so many cues impede understanding that change is needed, or interpreting new data effectively, instead reinforcing old views. A cognitive approach to innovation suggests why, and offers insights illustrated by accounts of three mature–industry innovation episodes. Technology entrepreneurship is shown as a quintessentially social activity, requiring joint efforts to interpret ambiguous data, joint understanding to sustain technology efforts, and persistent, coordinated endeavour to accomplish technological change. The nominally 'managerial' tasks of sensemaking, mindful alertness to anomalies, and the joint creation of a new shared cognitive context are broadly shared in these accounts, and stand out as the underpinnings of technological entrepreneurship.